Does Aristotle have a dialectical attitude in EE I 6? A negative answer - Mendonça, Fernando (2017)
In this paper, I analyse EE I 6, where Aristotle presented a famous methodological digression. Many interpreters have taken this chapter as advocating a dialectical procedure of enquiry. My claim is that Aristotle does not keep a dialectical attitude towards endoxa or phainomena in this chapter. In order to accomplish my goal, I shall show that EE I 6 does not provide enough evidence for the dialectical construal of it, and that this construal, in turn, hangs on some assumptions brought out from other Aristotelian works (EN and Top.), which do not provide good evidence either. By the examination of these assumptions, I intend to show that Aristotle is not carrying out any sort of dialectic, especially dialectic conceived as conceptual analysis seeking to save phainomena or endoxa.